2020
DOI: 10.3389/fonc.2019.01549
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNAs Involved in Resistance to Chemotherapy in Ovarian Cancer

Abstract: Ovarian cancer (OC) accounts for more than 150,000 deaths worldwide every year. Patients are often diagnosed at an advanced stage with metastatic dissemination. Although platinum-and taxane-based chemotherapies are effective treatment options, they are rarely curative and eventually, the disease will progress due to acquired resistance. Emerging evidence suggests a crucial role of long non-coding RNAs (lncRNAs) in the response to therapy in OC. Transcriptome profiling studies using high throughput approaches h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 181 publications
(136 reference statements)
0
43
0
Order By: Relevance
“…The CHRF-miR-10b axis described by us in this study has never been reported, neither in OC nor in the cisplatin resistance, and this signifies the innovative findings from our study. lncRNAs are increasingly being recognized to be involved in progression of human cancers 10 and even in the cisplatin resistance 13,24 and our results provide more value to such progress in the field. In our present study, CHRF was chosen from a few shortlisted lncRNAs.…”
Section: Discussionmentioning
confidence: 58%
“…The CHRF-miR-10b axis described by us in this study has never been reported, neither in OC nor in the cisplatin resistance, and this signifies the innovative findings from our study. lncRNAs are increasingly being recognized to be involved in progression of human cancers 10 and even in the cisplatin resistance 13,24 and our results provide more value to such progress in the field. In our present study, CHRF was chosen from a few shortlisted lncRNAs.…”
Section: Discussionmentioning
confidence: 58%
“…The dysregulation of lncRNAs in various types of cancer is a growing concern among researchers (27,28). Emerging studies have revealed that several lncRNAs are aberrantly expressed in NSCLC, and they have been recognized to perform oncogenic or anti-oncogenic activities during NSCLC progression (16,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In all of these studies, the EGFR transgenic constructs were generated by cloning the hEGFR cDNA that encodes the mutant transgenes, which therefore lacked the genetic information from the non-coding regions of the hEGFR gene. An increasing amount of evidence suggests that the gene non-coding regions are involved in predisposition, progression, invasiveness, metastasis, and drug resistance of malignant tumors and that their activity correlates with patient survival [ 14 , 15 , 16 , 17 , 18 ]. To develop lung cancer mouse models that closest resemble the human disease, here we generated two transgenic mice each of them carrying a mutant transgene that contains the full-length of genomic hEGFR, and thereby the mutant transgenes have the complete coding and non-coding genetic information of the hEGFR gene.…”
Section: Discussionmentioning
confidence: 99%